1997
DOI: 10.1086/310741
|View full text |Cite
|
Sign up to set email alerts
|

A Driving Mechanism for the Newly Discovered Class of Pulsating Subdwarf B Stars

Abstract: We present new calculations that strongly reinforce the idea-originally proposed by Charpinet et al.-that pulsation modes are driven through an opacity bump due to a local enhancement of the iron abundance in the envelopes of sdB stars. Our improved models incorporate nonuniform iron abundance distributions obtained through the condition of diffusive equilibrium between gravitational settling and radiative levitation. They also include special Rosseland opacity tables that take into account the large variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
293
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(315 citation statements)
references
References 17 publications
20
293
0
2
Order By: Relevance
“…marked "" He ] C ] Fe.ÏÏ An enhanced iron abundance at the surface might also increase the stellar radius slightly, thus decreasing the and this would also move the T eff , He ] C point somewhat redder. The iron enhancement seen in BHB stars does not appear to be present in the cooler EHB stars (see°6.1.3 ; also see Bedin et al 2000), but di †usion calculations (Charpinet et al 1997) show that the surface iron abundance can be enhanced to solar or even supersolar abundances at K, which is hotter T eff Z 30,000 than the canonical EHB but appropriate for blue-hook stars ; these iron enhancements o †er a possible driving mechanism for the pulsating sdB stars, which show solar iron abundances (Heber, Reid, & Werner 2000). Furthermore, it should be easier to enhance the iron abundance through radiative levitation if the atmosphere is mostly helium instead of hydrogen, because of the decrease in EUV opacity and the increase in the mean molecular weight in the atmosphere.…”
Section: Reddeningmentioning
confidence: 96%
“…marked "" He ] C ] Fe.ÏÏ An enhanced iron abundance at the surface might also increase the stellar radius slightly, thus decreasing the and this would also move the T eff , He ] C point somewhat redder. The iron enhancement seen in BHB stars does not appear to be present in the cooler EHB stars (see°6.1.3 ; also see Bedin et al 2000), but di †usion calculations (Charpinet et al 1997) show that the surface iron abundance can be enhanced to solar or even supersolar abundances at K, which is hotter T eff Z 30,000 than the canonical EHB but appropriate for blue-hook stars ; these iron enhancements o †er a possible driving mechanism for the pulsating sdB stars, which show solar iron abundances (Heber, Reid, & Werner 2000). Furthermore, it should be easier to enhance the iron abundance through radiative levitation if the atmosphere is mostly helium instead of hydrogen, because of the decrease in EUV opacity and the increase in the mean molecular weight in the atmosphere.…”
Section: Reddeningmentioning
confidence: 96%
“…One could simply enhance Fe uniformly through the entire stellar envelope (Charpinet et al 1996;Jeffery & Saio 2006a), but then the stellar evolution and pulsations would be unrealistically altered. A more sophisticated treatment assumes a diffusive equilibrium profile of Fe, see Charpinet et al (1997). These authors argued that the equilibrium state is reached on timescales much shorter than the sdB evolutionary timescale (∼10 5 compared to ∼10 8 years).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, two types of pulsating sdBs have been identified. V361 Hya stars consist of sdBs with short period photometric modulations (2−10 min), explained as low order (n), low degree ( ) p-modes (Kilkenny et al 1997;Charpinet et al 1997), which coexist with sdBs not observed to vary at the high end of the temperature range for these stars. At the cooler end, a much larger fraction of sdBs seem to be pulsating, but with longer periods (∼1 h) and low amplitudes of a few millimagnitudes at best (Green et al 2003).…”
Section: Introductionmentioning
confidence: 99%